PECULIARITIES OF THE APPLICATION OF THERMOGRAPHIC DEFECTOSCOPY FOR STEEL BUILDING STRUCTURES TAKING INTO ACCOUNT THEIR REAL STATE UNDER OPERATION CONDITIONS (Collection of scientific works «Modern structures of metal and wood», 2023)
The  article  presents  the  results  of  a  study  of  the  features  of  the  use  of thermographic  flaw  detection  for  steel  building  structures,  taking  into  account  their  actual  state under operating conditions. Since these structures are subjected to significant loads, they are subject to  failure,  including  cracking,  corrosion,  rupture,  and  other  damage.  Compliance  with  the  safe operation of steel structures is essential to ensure the safety of personnel and the normal production process.  Compliance  with  safety  rules  should  be  regular  and  systematic,  including  periodic inspections and diagnosing the condition of steel structures. Thermographic flaw detection methods consists in measuring the surface temperature of a structure using infrared cameras and detecting temperature anomalies that may indicate the presence of defects. The objective of the study is to increase  the  efficiency  of  using  the  active  thermography  method  for  examining  operated  steel structures. Identify possible difficulties that will arise in the application of this method, and develop recommendations to overcome the identified problems. The most significant aspect that can affect the  quality  of  thermographic  flaw  detection  is  a  characteristic  of  infrared  emission  of  the investigated structure’s part. The low value of this indicator leads to an increase in the amount of false data, which in turn reduces the reliability of the obtained results. Another equally important part of the work of an engineer in thermographic flaw detection is the choice of the method and place of heating the structure, which depends on specific cases and inspection tasks. Eventually, active  thermography  may  be  useful  and  effective  method  for  flaw  detection  of  steel  building structures. However, its application must be carried out in the context of all factors that may affect the accuracy and efficiency of the equipment concerned.